P4.118 "it's not a 'time spent' issue, it's a 'what have you spent your time doing?' issue…" patient opinions on potential implementation of point of care tests for multiple stis and antimicrobial resistance detection. (8th July 2017) - Fuller, Sebastian Suarez; Pacho, Agata; Harding-Esch, Emma; Sadiq, Syed Tariq
Abstract : Introduction: Advances in Point of Care Tests (POCTs), including the capacity to test for multiple Sexually Transmitted Infections (mSTIs) and Antimicrobial Resistance (AMR), have potential to transform sexual health clinic (SHC) services. Patient opinions of POCT implementation are needed to inform the redesign of SHC pathways to accommodate these new technologies. Methods: We conducted semi-structured interviews with a purposive sample of patients aged ≥16–44 in three SHCs across England. Analysis was based on the Framework method (NVivo 10). Patients were asked to describe their recent clinic visit and were then presented with different POCT designs and associated SHC pathway changes. Some proposed designs included potential to spend more time in clinic than currently, e.g. waiting for AMR results after a positive diagnosis. Results: From June 2015 - February 2016, 11 women, 12 heterosexual men and 8 men who have sex with men participated. Most patients were enthusiastic about receiving an accurate diagnosis and AMR result within one clinic visit. Women were more likely to question new technologies, report more previous visits and have higher expectations for their SHC experiences. Men and women strongly indicated willingness to wait in clinic for results if they perceived themselves at risk for infection (self-assessed as sexual risk-taking and/or having symptoms). All patients were willing to wait for AMR results following a positive result. Patient suggestions for POCT pathway implementation included: targeting POCTs to those concerned they are infected and providing information on steps and time involved for new pathways. Conclusion: Patients' willingness to wait in clinic, explained as dependent on a self-assessed risk for infection, provides nuanced understanding of patients' priorities for care. Patient suggestions that specific, directed messaging from SHCs may allow acceptability of various changes related to POCT adoption gives guidance for implementation. We recommend further research when these tests are made available, to assess these theories in practice.